Progress in delivering SDG6: Safe water and sanitation - Jay Rajapakse; Miriam Otoo; George Danso (Cambridge Prisms: Water, 2023)
Sustainable development goal 6 (SDG6) is to ensure the availability and sustainable management of safe water and sanitation for all by 2030. The water and sanitation goals are defined by 8 targets that specify the goals, and the progress towards the 2030 Agenda for sustainable development is measured with 11 indicators as metrics by which the world aims to track whether these targets are achieved. This article presents the current global progress against these indicators. During 2015–2020, globally the proportion of population with access to safely managed drinking water services improved from 70% to 74%, safely managed sanitation services grew from 47% to 54%, and handwashing facilities with soap and water increased from 67% to 71%. Among the world’s regions, many Sub-Saharan African countries may not be able to achieve even the target of basic water and sanitation services by 2030, with 61% access to basic water supply (compared to 90% globally) and 31% for sanitation (compared to 84% globally). There are also significant inequalities between rural and urban access to these services. Eight out of 10 people without basic water services lived in rural areas, while safely managed sanitation services reached 62%of the world’s urban population, but only 44% of its rural population. The world is on track to eliminate open defecation by 2030. The business-as-usual rates of progress would need to double for the world to achieve universal coverage with basic water and sanitation services by 2030. To achieve universal safely managed services, rates would need to quadruple. To achieve universal access to safely managed drinking water by 2030 in low- and middle-income countries, the current rates would need to increase ten-fold. Some barriers to progress are discussed.